Black sexual economies : race and sex in a culture of capital - Davis, Adrienne D., 1965- (New Black studies series., 2019)
"A daring collaboration among scholars, Black Sexual Economies challenges thinking that sees black sexualities as a threat to normative ideas about sexuality, the family, and the nation. The essays highlight alternative and deviant gender and sexual identities, performances, and communities, and spotlights the sexual labor, sexual economy, and sexual agency to black social life. Throughout, the writers reveal the lives, everyday negotiations, and cultural or aesthetic interventions of black gender and sexual minorities while analyzing the systems and beliefs that structure the possibilities that exist for all black sexualities. They also confront the mechanisms of domination and subordination attached to the political and socioeconomic forces, cultural productions, and academic work that interact with the energies at the nexus of sexuality and race."--